MAFIC ROCKS FROM THE SEDIMENTARY BRECCIAS ASSOCIATED TO THE BALAGNE OPHIOLITIC NAPPE (NORTHERN CORSICA): GEOCHEMICAL FEATURES AND GEOLOGICAL IMPLICATIONS - Marroni, Michele; Pandolfi, Luca; Saccani, Emilio (Ofioliti, 2001)
In the Balagne area (Northern Corsica), two main coarse-grained deposits characterized by the presence of mafic rocks are recognized. The first is represented by the Toccone breccia (Late Cenomanian) belonging to the succession of the Balagne ophiolitic nappe, whereas the second, referred to as Volparone breccia (post-Jurassic), occurs as a slice at the base of the same nappe and displays no relationships with others lithologies. Both breccias can be regarded as deposits located close to their source area, as suggested by their sedimentological/stratigraphical features. Even if not coeval, these breccias were probably supplied by the same source area consisting of a metamorphic basement intruded by granitoids and covered by carbonate deposits. The recognized lithologies suggest that its source area was represented by a domain belonging to the Corsica continental margin. The Toccone and Volparone breccias are both characterized by mafic rocks, wich can be classified as transitional to tholeiitic within-plate basalts. It is noteworthy that clasts of ophiolites are completely lacking. The mafic rocks preserved as clasts in the Toccone and Volparone breccias are the remnants of a magmatism connected with the crustal thinning processes. This magmatism developed during the Late Permian-Jurassic before the opening of the Ligure-Piemontese oceanic basin. This magmatism probably developed in an area of the Hercynian basement that in the Late Jurassic became located in the oceanward side of the Corsica continental margin, i.e. the source area of the studied breccias.